Context scenarios and their usage for the construction of socio-technical energy scenarios. (15th September 2016) - Weimer-Jehle, Wolfgang; Buchgeister, Jens; Hauser, Wolfgang; Kosow, Hannah; Naegler, Tobias; Poganietz, Witold-Roger; Pregger, Thomas; Prehofer, Sigrid; von Recklinghausen, Andreas; Schippl, Jens; Vögele, Stefan
Abstract: Model-based energy scenarios are a widely used tool for supporting economic and political decision makers. The results of energy modeling and the conclusions deduced therefrom, however, depend on the model input data derived from framework assumptions about future developments in the embedding society, which are deeply uncertain in the long term. The challenge to deal with this 'context uncertainty' in a systematic and comprehensive manner has only recently started to attract intensified attention in energy research; the search for appropriate methods is ongoing. This paper proposes a new concept for the construction of socio-technical energy scenarios, which combines familiar environmental modeling approaches with new developments in qualitative scenario methodology, and demonstrates the possible application of the concept in model-based energy scenario construction. Highlights: Model-based energy scenarios depend on assumptions about the embedding society. We propose a method to address the complex uncertainty of these assumptions. The method combines elements of qualitative and quantitative systems analysis. This eventually leads to the development of socio-technical energy scenarios. A concept demonstration shows the practical application of the method.